Navigating Environmental Uncertainty: Corporate Governance’s Role in Shaping Capital Structure - Wardhani, Dian Kusuma; Anandita, Rissa; Choirunnisa, Felisma (CV. Ulil Albab Corp, 2025)
The aims of this research is to provide empirical evidence about the impact of environmental uncertainty on capital structure, while also considering the potential moderating influence of corporate governance. Uncertainty in the business environment due to the 2018 US-China trade war damaged Indonesian company capital structure planning. The total 313 manufacturing firms listed on the IDX between 2019 to 2023 were tested using multiple linear and moderated regression analyses. The research found that corporate governance mitigates the negative effect of environmental uncertainty on capital structure. The research findings support the pecking order theory by providing evidence that the capital structure starts from the lowest-cost funding sources to be efficient. Furthermore, this study supports the agency theory that corporate governance actively monitors management using corporate debt during environmental uncertainty. It can avoid management's deviant behavior, avoiding bankruptcy and the risk of company default.